P010 The Modulation of Error Detection in Dystonia via TDCS. Issue 3 (March 2017) - Chen, J.-C.; Rothwell, J.; Edwards, M.
Abstract : Dystonia is a group of hyperkinetic movement disorders which the main character is involuntary sustained muscle contraction results in twisting and repetitive movements or abnormal postures. In addition to the abnormal movements, sensory impairment has been demonstrated to be major feature in this disease (Ghika et al., 1993; Stamelou et al., 2012; Byl et al., 1996; Bara-Jimenez et al., 1998; Elbert et al., 1998). Also, an increasing amount of evidence implicates a relationship between dystonia and the cerebellum (Rumbach et al., 1995; O'Rourke et al., 2006; Waln and LeDoux, 2010). We have demonstrated that tDCS over the cerebellum is able to bidirectionally modulate the MMN, an event related potential reflecting the automatic detection process in our brain. In this study, we further measured the MMN from 10 cervical dystonia patients before and after cathodal tDCS in order to investigate the role of the cerebellum in error prediction and dystonia. The result showed that there was no modulation of MMN after cerebellar tDCS. This could reflect an abnormality in plasticity of the cerebellum in dystonia patients. Therefore, we can suggest that the cerebellum might be an important area in impaired prediction error in dystonia.